A child's garden of verses - Stevenson, Robert Louis, 1850-1894; Smith, Jessie Willcox, 1863-1935 (New York : Children's Classics, 1985)
A collection of poems evoking the world and feelings of childhood.
Keywords: Children's poetry, English; Scottish poetry